Marketing to Gen Z : the rules for reaching this vast, and very different, generation of influencers - Fromm, Jeff; Read, Angie (AMACOM, 2018)
Drawn from original quantitative research and interviews, this timely and practical book paints a fascinating portrait of the newest buyers now entering the scene and offers dozens of examples and insights for connecting and conversing with them.